2023
DOI: 10.1177/11795735231181467
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Phenotypes of IRF2BPL Gene Variants: A Report of Four Novel Variants

Abstract: IRF2BPL gene variants have recently been associated to developmental disability and epilepsy in children and movement disorders in adults. So far, only few cases have been reported; here we present four novel cases identified by exome sequencing, while investigating developmental delay, adult-onset cerebellar ataxia or regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…To further delineate the potential genotype and phenotype correlations of the rare mutations in IRF2BPL , we combined our data with results from previous studies to clarify whether dystonia or other non‐epilepsy clinical characteristics are observed in patients having mutations in the poly Q domain of IRF2BPL . Combining 60 patients with IRF2BPL mutations previously described in the literature and the patient reported in the present study (Table S2), 5–7,9–11,24–38 we created four subgroups (Table 1) based on the locations of the identified mutations in the protein: the N‐terminal poly Q domain ( n = 29), poly A domain ( n = 2), variable region ( n = 28), and the C‐terminal C3HC4 type ring finger domain ( n = 2). Among these patients, only four individuals were documented to have affected parents with heterozygous variant following an autosomal‐dominant inheritance trait, indicating a high rate of de novo mutation in this gene.…”
Section: Resultsmentioning
confidence: 99%
“…To further delineate the potential genotype and phenotype correlations of the rare mutations in IRF2BPL , we combined our data with results from previous studies to clarify whether dystonia or other non‐epilepsy clinical characteristics are observed in patients having mutations in the poly Q domain of IRF2BPL . Combining 60 patients with IRF2BPL mutations previously described in the literature and the patient reported in the present study (Table S2), 5–7,9–11,24–38 we created four subgroups (Table 1) based on the locations of the identified mutations in the protein: the N‐terminal poly Q domain ( n = 29), poly A domain ( n = 2), variable region ( n = 28), and the C‐terminal C3HC4 type ring finger domain ( n = 2). Among these patients, only four individuals were documented to have affected parents with heterozygous variant following an autosomal‐dominant inheritance trait, indicating a high rate of de novo mutation in this gene.…”
Section: Resultsmentioning
confidence: 99%